A Multidisciplinary Approach to Supply Chain Agility: Conceptualization and Scale Development. Issue 2 (11th June 2013) - Gligor, David M.; Holcomb, Mary C.; Stank, Theodore P.
<x xml:space="preserve">Abstract</x> Although agility has been identified as one of the most important issues of contemporary supply chain management, the theoretical basis for understanding supply chain agility is fragmented. This research addresses the gap related to the ambiguity surrounding the dimensions and definitions of firm supply chain agility by employing a multidisciplinary literature review to gain an in‐depth understanding of agility. In addition, a comprehensive measurement instrument that draws on the foundations of social and life science theory is developed and empirically validated. The results of the research indicate that firm supply chain agility is composed of five distinct dimensions including alertness, accessibility, decisiveness, swiftness, and flexibility. Based on these elements, a comprehensive definition of firm supply chain agility is developed for further theoretical testing of the concept.